Simulating scratch behavior of polymers with mesoscopic molecular dynamics - Hilbig, Travis (2013)
Part replacement and repair is needed in structures with moving parts because of scratchability and wear. In spite of some accumulation of experimental evidence, scratch resistance is still not well understood. We have applied molecular dynamics to study scratch resistance of amorphous polymeric materials through computer simulations. As a first approach, a coarse grain model was created for high density polyethylene at the mesoscale. We have also extended the traditional approach and used real units rather than reduced units (to our knowledge, for the first time), which enable an improved quantification of simulation results. The obtained results include analysis of penetration depth, residual depth and recovery percentage related to indenter force and size. Our results show there is a clear effect from these parameters on the tribological properties. We also discuss a "crooked smile" effect on the scratched surface and the reasons for its appearance.